P-263 Enhancing the recognition of palliative care education for district nurses – 'walking side by side'- a programme of engagement between hospice and community. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Parkes, Nicola; Moran, Helen; Roberts, Sarah; Huttley, Julie
Abstract : The numbers of professionals being able to support patients and their families will have future challenges. Across Blackpool Fylde and Wyre many patients end up being admitted to the acute setting in circumstances that could have been avoided. The district nursing workforce has seen many changes in our area, with less experienced staff being exposed to a number of clinical conditions that would have been previously managed in the acute setting. The knowledge and understanding around palliative care and its management has become fragmented, with time pressures and workload demands preventing staff from attending training. We considered how as a hospice and centre for excellence how we could support our community colleagues to enhance their knowledge and skill, to create better links to enable a range of staff to provide 'hospice' care to patients and families in their own homes and to also provide an opportunity for staff to be supported to discuss clinical cases with our CNS Team to enhance shared learning. The programme of engagement offers bite-size education sessions allowing the opportunity to explore aspects of palliative care in bundles of educational topics. A community based programme that enables a range of staff to focus on a clinical aspect of care, time for reflection, and supported discussion to increase understanding around accurate assessment, knowledge and management of palliative care patients and their families to improve quality of care and patient outcomes. The programme launched in April 2017. All 13 district nursing teams have signed up, to date there have been 183 staff trained. These results provide proof that as a hospice we can influence care by having a user-friendly based education strategy delivered into the community which could be effectively duplicated in other settings.